SUBMICROSCOPIC CHANGES OF AERO-HEMATIC BARRIER COMPONENTS IN THE LATER PERIODS AFTER EXPERIMENTAL THERMAL TRAUMA - Небесна, З.М. (World of Medicine and Biology, 2014)
In the experiment on white rats submicroscopic components of the aero-hematic barrier of respiratory lungs was studied in the stage of late toxemia and septicotoxemia after thermal trauma, ІІІ degree. Established that in the later stages after severe burns, significant destructive changes of ultrastructure of the alveolar wall components and blood capillary.
Keywords: aero-hematic barrier; ultrastructural changes; thermal trauma; late toxemia